2020
DOI: 10.1101/2020.07.20.20157149
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Association of contact to small children with mild course of COVID-19

Abstract: It is known that severe COVID-19 cases in small children are rare. If a childhood-related infection would be protective against severe course of COVID-19, it would be expected that adults with intensive and regular contact to small children also may have a mild course of COVID-19 more frequently. To test this hypothesis, a survey among 4,010 recovered COVID-19 patients was conducted in Germany. 1,186 complete answers were collected. 6.9% of these patients reported frequent and regular job-related contact to ch… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 2 publications
0
8
0
Order By: Relevance
“…We only found one study which touched on this question, a survey of exposures among people who had recovered from SARS-CoV-2. 16 Ours is the first cohort study of which we are aware to formally test this hypothesis, for which the findings provide a degree of support.…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…We only found one study which touched on this question, a survey of exposures among people who had recovered from SARS-CoV-2. 16 Ours is the first cohort study of which we are aware to formally test this hypothesis, for which the findings provide a degree of support.…”
Section: Discussionmentioning
confidence: 78%
“…The primary exposure was the number of children aged 0 to 11 (hereafter referred to as young children) in each household. In additional analyses, risks for household members of pre-school children (aged 0-4) and primary school-aged children (aged 5-11) were examined separately as were the risks of sharing a household with older children (aged [12][13][14][15][16][17] and with other adults.…”
Section: Exposurementioning
confidence: 99%
See 2 more Smart Citations
“…In line with this hypothesis, adults aged 15 to 44 years (having presumably an increased probability of living with young children) have been shown to have higher antibody titers against the HCoV-OC43 N protein than older adults 18 . Also, supporting the notion of a rather immunological than a purely epidemiological phenomenon, a German study among over 4’000 COVID-19 patients suggested a less complicated disease course for those with frequent contact to children 19 . This hypothesis was partially confirmed by a recent study that demonstrated pre-existing humoral immunity (including neutralizing antibodies) to be particularly prevalent in children and adolescents 20 .…”
Section: Discussionmentioning
confidence: 79%